PCSK9 variant, long-chain n-3 PUFAs, and risk of nonfatal myocardial infarction in Costa Rican Hispanics - Yu, Z.; Huang, T.; Zheng, Y.; T. Wang; Heianza, Y.; Sun, D.; Campos, H.; Qi, L. (Am J Clin NutrAm J Clin NutrAm J Clin Nutr, 2017)
Background: Previous studies have indicated that the cardioprotective effects of long-chain (LC) n-3 (omega-3) polyunsaturated fatty acids (PUFAs) may vary across various ethnic populations. Emerging evidence has suggested that the gene-environment interaction may partly explain such variations. Proprotein convertase subtilisin/kexin type 9 (PCSK9) was shown to have a mutually regulating relation with LC n-3 PUFAs and also to reduce the risk of cardiovascular diseases (CVDs). Therefore, we hypothesized that certain PCSK9 genetic variants may modify the association between LC n-3 PUFA intake and CVD risk.Objective: We determined whether a PCSK9 variant (rs11206510), which has been identified for early onset myocardial infarction (MI), modified the association of LC n-3 PUFAs with nonfatal MI risk in Costa Rican Hispanics.Design: We analyzed cross-sectional data from 1932 case subjects with a first nonfatal MI and 2055 population-based control subjects who were living in Costa Rica to examine potential gene-environment interactions. Two-sided P values <0.05 were considered significant.Results: We observed a significant interaction between the PCSK9 rs11206510 genotype and LC n-3 PUFA intake on nonfatal MI risk (P-interaction = 0.012). The OR of nonfatal MI was 0.84 (95% CI: 0.72, 0.98) per 0.1% increase in total energy intake from LC n-3 PUFAs in protective-allele (C-allele) carriers, whereas the corresponding OR (95% CI) in non-C-allele carriers was 1.02 (95% CI: 0.95, 1.10). Similar results were observed when we examined the association between docosahexaenoic acid, which is one type of LC n-3 PUFA, and nonfatal MI risk (P-interaction = 0.003).Conclusion: LC n-3 PUFA intake is associated with a lower risk of nonfatal MI in C-allele carriers of PCSK9 rs11206510 (n = 799) but not in non-C-allele carriers (n = 3188).
Keywords: *Diet; *Gene-Environment Interaction; *Genotype; *Myocardial Infarction/etiology/genetics/prevention & control; Aged; Alleles; Costa Rica; Cross-Sectional Studies; Docosahexaenoic Acids/therapeutic use; Energy Intake; Epigenesis, Genetic; Fatty Acids, Omega-3/*therapeutic use; Feeding Behavior; Female; Genetic Predisposition to Disease; Hispanic Americans/*genetics; Humans; Male; Middle Aged; Odds Ratio; Polymorphism, Single Nucleotide; Proprotein Convertase 9/*genetics